COBO SJ., Bemabé, History of the Inca Empire. An account of the Indians custom and their origin with a treatise on Inca legends, history, and social institutions; translated and edited by Roland Hamilton. Foreword· by John Rowe.University of Texas Press, Austin and London, 1979; XXII, 279 págs. - Pease, Franklin (1981)
No contiene resumen